Looking at the other side: working conditions in Portuguese courts - Dias, João Paulo (2024)
Accepted version of the article published in: Dias JP, Casaleiro P, Gomes C, Jesus F, Lima TM, Queirós F, Relvas AP, Sotero L, Henriques M, and Verzelloni L (2024). Looking at the other side: working conditions in Portuguese courts. International Journal of Law in Context 20, 246–266. https://doi.org/10.1017/S1744552324000028